The Circular Economy within Hospital Units in Romania - Rareş Cosmin NICORICI; Ana - Maria BORES (Communications of International Proceedings, 2021)
The unlimited use of natural resources is moving at a rapid pace towards the day when the regenerative capacity of the Earth is exceeded by what is consumed. The concept of circular economy will primarily help to protect natural resources and the environment and thus society as a whole would evolve at a sustainable and healthy pace. At the same time, the transition from the linear to the circular economy will support the achievement of sustainable development goals. In fact, the transition to the circular economy comes with many direct health benefits.The transition to a circular economy both within and beyond hospital units, where the value of products, materials and resources is kept in the economy for as long as possible and waste generation is kept to a minimum, is a key contribution to the EU's efforts. development of a sustainable economy and should result from the involvement of each economic operator as well as the territorial units of the state, regarding low carbon dioxide, efficient in terms of resource use and competitive. Such a transition is an opportunity to transform economy and generate new and sustainable competitive advantages in Europe, but also to create top services by attracting new investors to the market.
Keywords: Circular Economy; Hospital Unit; Cost Saving; Efficiency; Effectiveness